Smooth Path or Long and Winding Road? How Institutions Shape the Transition from Higher Education to Work - Kathrin Leuze (Budrich UniPress, 2010)
The book uses a comparative study of Germany and Britain to reveal how national institutions shape the labour market careers of higher education graduates. It identifies four institutional spheres that are important: the structure of higher education systems, the content of study, the structure of graduate labour markets, and labour market flexibility. Due to country differences, the transition from higher education to work in Germany follows a smooth path, while in Britain it is more comparable to a long and winding road.
Additional information: Zugl.: Dissertation, Universität Bremen, 2007
Keywords: 330; national institutions; labour market; higher education; Germany; Great Britain; public sector; unemployment; vocational education